5. 犖犖犖犖巌権犖迦検犢仰犖о犢仰犖犖犖犢 u 犢犖ム鍵 v 犖÷元犖犖巌絹犖犖迦犢犖犖犖迦犢犖犖朽権犖о犖園 犖犢犖犢犖犢犖÷厳犢犖 犢仰犖о犢仰犖犖犖犢犖犖園犖犖犖犖 犖犢犖犖犖犖犖迦犖犖園 犢犖ム鍵犖÷元犖ム弦犖犖犖 犢犖犖犖迦犢犖犖朽権犖о犖園 u 犢犖ム鍵 v 犖÷元犖犖巌絹犖犖迦犖犖犖犖犖園犖犢犖迦検犖犖園 犖犢犖犢犖犢犖÷厳犢犖 犢仰犖о犢仰犖犖犖犢犖犖園犖犖犖犖 犖犢犖犖犖犖犖迦犖犖園 犢犖ム鍵犖÷元犖犖園硯犖ム弦犖犖犖犢犖犖犖迦犖犖犖犖犖園犖犢犖迦検 u = v 犖犢犖犢犖犢犖÷厳犢犖 犖 .) 犢仰犖о犢仰犖犖犖犢犖犖園犖犖犖犖犖犢犖犖犖÷元犖犖犖迦犢犖犢犖迦犖園 犖 .) 犢仰犖о犢仰犖犖犖犢犖犖園犖犖犖犖犖÷元犖犖巌絹犖犖迦犢犖犖朽権犖о犖園
6. 犖犖犖犖巌権犖迦検 ( 犖犢犖 ) 犖犖巌犖犖犖犖犖 u 犖犖劇賢犢仰犖о犢仰犖犖犖犢犖犖朽犖÷元犖犖犖迦犢犖犢犖迦犖園 u 犢犖犢犖÷元犖犖巌絹犖犖犖犖犢犖迦検犖犖園 u 犢犖ム鍵犖犖巌犖犖犖犖犖 u 犢犖犖朽権犖犢犖犖犖犢犖о権 - u 犢仰犖о犢仰犖犖犖犢犖犖項犖∇ 犖犖劇賢犢仰犖о犢仰犖犖犖犢犖犖朽犖÷元犖犖犖迦犢犖犢犖迦犖園 0 犖犖犖劇賢犢仰犖о犢仰犖犖犖犢 犖犖朽犖÷元犖犖伍犖犖項犢犖犖巌犖÷犢犖犢犖ム鍵犖犖伍犖犖巌犖犖犖伍犖犖朽犖犖伍犢犖犖朽権犖о犖園 犢犖犖朽権犖犢犖犖犖犢犖о権 0
7. 犖犖÷犖園犖巌犖犖犖犖迦牽犖犖о犢仰犖о犢仰犖犖犖犢 犢犖犢 u , v 犢犖ム鍵 w 犢犖犢犖犢仰犖о犢仰犖犖犖犢犢犖犢犢犖犖犖萎犖迦 犢犖ム犖 1. u + v 犢犖犢犖犢仰犖о犢仰犖犖犖犢犢犖犖犖萎犖迦 2. u + v = v + u 3. (u + v) + w = u + (v + w ) 4. u + 0 = 0 + u = u 5. u + (-u) = (-u) + u = 0
8. 犖犖迦牽犖犖項犢仰犖о犢仰犖犖犖犢犖犢犖о権犖犢犖犖ム顕犖犢 犖犖犖犖巌権犖迦検 犢犖犢 a 犢犖犢犖犖犖橿犖о犖犖犖巌 犢犖ム鍵 u 犢犖犢犖犢仰犖о犢仰犖犖犖犢 犢犖ム犖 1. 犖犖ム犖項犖犖萎見犖о犖迦 a 犖犖園 u 犢犖犖朽権犖犢犖犖犖犢犖о権 au 2. 犖犢犖 a = 0 犢犖ム犖 au = 0 3. 犖犢犖 a > 0 犢犖ム犖 au 犖犖萎検犖朽犖犖迦犢犖犢犖迦犖園 |a| |u | 犢犖ム鍵犖÷元犖犖巌絹犖犖迦犢犖犖朽権犖о犖園 u 4. 犖犢犖 a < 0 犢犖ム犖 au 犖犖萎検犖朽犖犖迦犢犖犢犖迦犖園 |a| |u | 犢犖ム鍵犖÷元犖犖巌絹犖犖迦犖犖犖犖犖園犖犢犖迦検犖犖園 u 犖犢犖犖犖園犢犖犖 1.) 1u = u 2.) (-1)u = -u